Ebbe Flatau. Litauen I / Lietuva I - Vaicekauskienė, Loreta (Scandinavistica Vilnensis, 2023)
Litauen I / Lietuva I is a bilingual Danish-Lithuanian publication of the first part of the autobiography by Ebbe Flatau (b. 1938 in Kaunas), the first Danish lecturer at the Scandinavian Department at Vilnius University. This engaging autobiographical account delves into the author’s family history, which is intricately related to interwar Lithuania. Ebbe Flatau was born into a Danish family that operated a farm close to Kaunas: agricultural reforms and political agreements between Denmark and Lithuania during that period attracted a considerable colony of Danes to the country. In this edition, the previously unpublished original text is presented in parallel with its Lithuanian translation and is supplemented with illustrations, commentary, audio excerpts from conversations with Ebbe Flatau, as well as appendices that include archival documents, Danish and Lithuanian interwar press articles, and documentaries.Šis dvikalbis, danų ir lietuvių kalbomis parengtas leidinys – tai pirmojo Vilniaus universiteto Skandinavistikos katedros danų kalbos lektoriaus Ebbes Flatau (g. 1938 m. Kaune) autobiografijos dalies, pavadintos Litauen I, publikacija. Įtraukiantis autobiografinis pasakojimas pristato su tarpukario Lietuva susijusią autoriaus šeimos istoriją. To laikotarpio žemės ūkio reformos bei politiniai Danijos ir Lietuvos susitarimai į Lietuvą pritraukė nemažą danų koloniją ir Ebbe Flatau gimė viename iš Lietuvoje įsteigtų daniškų ūkių. Ebbes Flatau autobiografijos tekstas čia publikuojamas pagrečiui su vertimu į lietuvių kalbą ir papildytas iliustracijomis, komentarais, pokalbių su autoriumi įrašų ištraukomis bei priedais – archyviniais dokumentais, danų ir lietuvių tarpukario spaudos straipsneliais, dokumentiniais filmais.Sudarymas, vertimas iš danų kalbos, komentarai, priedai, iliustracijos / Editing, translation from Danish, comments, appendices, and illustrations by Loreta VaicekauskienėKomentarai, priedai, iliustracijos / Comments, appendices, and illustrations by Norbertas ČerniauskasVertimas į danų kalbą, priedai, iliustracijos / Translation into Danish, appendices, and illustrations by Dixie Simonsen
Keywords: -